2017
DOI: 10.1371/journal.pone.0183664
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the protective effects of metformin in experimental myocardial infarction

Abstract: Metformin improves cardiovascular prognosis in patients with diabetes mellitus, compared to alternative glucose-lowering drugs, despite similar glycemic control. Direct cardiovascular protective properties have therefore been proposed, and studied in preclinical models of myocardial infarction. We now aim to critically assess the quality and outcome of these studies. We present a systematic review, quality assessment and meta-analysis of the effect of metformin in animal studies of experimental myocardial infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…In an animal experiment, DPP4 inhibitors reduced LVM more than vildagliptin [ 16 ], and it has been indicated that the administration of incretin preparations has anti-inflammatory and LVM-lowering actions [ 44 , 45 ]. While metformin is believed to exhibit anti-inflammatory and anti-oxidative actions, it has been reported that no LVM-lowering effect was observed [ 19 , 46 ]. In the present study, while the administration of these drugs did not lower LVM significantly compared with the placebo, the results lack consistency with those of previous studies, and we believe that further examination is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal experiment, DPP4 inhibitors reduced LVM more than vildagliptin [ 16 ], and it has been indicated that the administration of incretin preparations has anti-inflammatory and LVM-lowering actions [ 44 , 45 ]. While metformin is believed to exhibit anti-inflammatory and anti-oxidative actions, it has been reported that no LVM-lowering effect was observed [ 19 , 46 ]. In the present study, while the administration of these drugs did not lower LVM significantly compared with the placebo, the results lack consistency with those of previous studies, and we believe that further examination is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In addition metformin improves the secondary endpoints left ventricular ejection fraction (LVEF) and left ventricular end systolic diameter (LVESd). These results indicate a cardio protective effect of metformin [24]. Experimental studies and clinical observations provide an increasing number of arguments confirming the numerous benefits of metformin usage in patients with heart failure.…”
Section: 3mentioning
confidence: 53%
“…Cardioprotective effects of metformin were also demonstrated in rat model of chronic HF (Wang et al, 2011 ). However, a recent meta-analysis validates with caution this beneficial impact only on experimental myocardial infarction (Hesen et al, 2017 ). And this is the line with observations led in clinical trials.…”
Section: Discussion: Therapeutic Strategiesmentioning
confidence: 99%